Key role of moss in supplementing nitrogen for plant growth under warming in a permafrost ecosystem - Wei Zhou; Yuxuan Bai; Yuhong Xie; Bin Wei; Wolfgang Wanek; Kathrin Rousk; Genevieve Noyce; Dianye Zhang; Yunfeng Peng; Yuanhe Yang (Proceedings of the National Academy of Sciences, 2026)
Enhanced plant productivity under climate warming may partially offset soil carbon losses in cold ecosystems, but this compensation depends on whether soil nitrogen (N) supply can keep pace with the increased N demand associated with accelerated plant growth. However, it remains unclear whether existing soil N supply processes are sufficient to support this rising plant N demand. Based on a unique whole-ecosystem warming experiment in the permafrost region on the Tibetan Plateau, we assess 43 variables encompassing plant N demand and soil N supply. After 2 y of warming, plant N demand significantly increases, while leaf N resorption remains unchanged, indicating a heightened reliance on external soil N inputs. Among all quantified N-supply processes, moss-associated biological N fixation is the only process that responds positively to warming, providing partial compensation for the elevated plant N demand over the two experimental years. This enhancement is associated with warming-driven changes in moss functional traits that likely expand colonization niches and increase carbon availability for diazotrophs, coupled with a warming-induced increase in the breadth and intensity of taxon-level 15 N incorporation into the DNA of N-fixing bacteria. These findings highlight that moss-associated N fixation may act as an early contributor in helping satisfy the elevated plant N demand under warming, offering insights into understanding the dynamics of vegetation productivity and permafrost carbon-climate feedback through the lens of moss–soil–microbial interactions.